Pengaruh Independensi, Profesionalisme, Pengalaman Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Koperasi Simpan Pinjam Di Kabupaten Rembang - Mahardika Tustha Prana; Banu Witono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect of independence, professionalism, work experience, and work motivation on the performance of employees of savings and loan cooperatives in Rembang Regency. This study used quantitative methods. The population selected in this study is all employees in the savings and loan Cooperatives located in Rembang Regency, which has the position of marketing, administration, cashier, staff, deputy leaders and leaders. Sampling using sampling techniques with certain criteria called purposive sampling. The sample in this study was 166 employees of savings and loan Cooperative of Rembang Regency. The results of this study is that there is an influence of independence, professionalism, work experience, and work motivation on employee performance.